Optimizing the Surgical Phase of Dental Implants Optimization of the Surgical Phase of Dental Implantation Based on Computer Modelling (Eurasian Medical Research Periodical, 2022)
Reducing the number of complications after dental implantation remains an urgent problem in dentistry. All risk factors can be divided into general - smoking, systemic pathology, condition after radiation therapy, etc., and local - poor oral hygiene, periodontal disease, iatrogenic conditions, design and quality of processing of the transgingival part of the implant. Understanding the course of inflammatory and destructive processes around a dental implant after its placement directs scientists and implant manufacturers to improve already used conservative and surgical methods of treatment of these diseases, as well as to pay more attention to the prevention of this pathology and, consequently, to the risk factors of its development. The development of new surgical and prosthetic techniques and the creation of new implant systems will increase the life span of implant-supported dentures and improve the quality of life of patients.